2003
DOI: 10.1063/1.1605093
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bond dynamics in liquid methanol

Abstract: A Car–Parrinello molecular dynamics simulation has been performed on fully deuterated liquid methanol. The results are compared with the latest available experimental and theoretical data. It is shown that the liquid is aggregated in chains of hydrogen bonded molecules. The structure of the aggregates is characterized and it is found that the dynamics includes a fast and a slow regime. The weak H bond formed by the methyl group hydrogens and oxygen atom of surrounding molecules has been characterized. The impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
186
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(201 citation statements)
references
References 62 publications
14
186
1
Order By: Relevance
“…Thus in a mixture of CH 3 OH and H 2 O, we would expect a mixture of different hydrogen bond coordination numbers ranging from 1 to 3. In fact, computational studies have shown that the mean dipole moment of the CH 3 OH molecule depends on the number of hydrogen bonds the molecule makes with its nearest neighbours and that the dipole moment increases with increasing number of hydrogen bonds, suggesting substantial rearrangement of the molecular electron density 38 . The authors point out that the observed trend in liquid CH 3 OH closely resembles that of liquid H 2 O.…”
Section: Ch 3 Oh As a Proton Donor/acceptormentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in a mixture of CH 3 OH and H 2 O, we would expect a mixture of different hydrogen bond coordination numbers ranging from 1 to 3. In fact, computational studies have shown that the mean dipole moment of the CH 3 OH molecule depends on the number of hydrogen bonds the molecule makes with its nearest neighbours and that the dipole moment increases with increasing number of hydrogen bonds, suggesting substantial rearrangement of the molecular electron density 38 . The authors point out that the observed trend in liquid CH 3 OH closely resembles that of liquid H 2 O.…”
Section: Ch 3 Oh As a Proton Donor/acceptormentioning
confidence: 99%
“…In CH 3 OH the vibrational spectra of the O-H, C-H and the C-O stretch are sensitive to the interaction between nearest neighbours. The interactions between CH 3 OH and H 2 O have been studied in mixed CH 3 OH/H 2 O liquids [29][30][31][32] , heterodimers [33][34][35] and small clusters both in the gas phase and in matrix isolation studies 33,34 , supported with extensive computational studies [36][37][38][39][40][41][42][43][44] . The O-H stretch has been used extensively to study hydrogen bonding between H 2 O and CH 3 OH in dimers, matrix isolation and in clusters, however, in the bulk condensed and liquid phases this poses a problem as the broad absorption bands due to the O-H stretching frequencies of both CH 3 OH and H 2 O overlap.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 It has therefore been thought that something similar could be occurring in the liquid phase and be responsible for its peculiar behavior. Several numerical simulations [18][19][20][21][22][23] and neutron diffraction experiments [24][25][26] have produced data that support this view. On the other hand, experimental results of neutron diffraction, 27,28 x-ray scattering, 29,30 and x-ray emission spectroscopy 31 have been taken to support the existence of cyclic clusters of methanol in the liquid phase.…”
Section: Introductionmentioning
confidence: 69%
“…Kashtanov et al 31 have suggested that numerical simulations could be using potentials that are not able to reproduce the hydrogen bonding network in ring structures. There is a substantial number of numerical simulations of methanol [18][19][20][21][22][23][32][33][34] and some of them which include polarizability [35][36][37][38] have shown the need for refined potentials.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] In liquid MeOH, the noncoincidence effect is 94 cm −1 , 18 about twice the value of the coupling estimated here from the simultaneous absorption of MeOH dissolved in MeOD. The discrepancy may be due to the fact that in dilute MeOH:MeOD an OH group involved in simultaneous absorption interacts with only one other OH group, whereas in liquid MeOH each OH group interacts with at least two other OH groups, 23,24 so that the Raman noncoincidence effect observed in liquid MeOH arises from multiple OH-OH couplings. The experimentally determined OH-OH coupling may be compared to the transition-dipole coupling between the two OH groups, which is, in general, the dominant contribution to intermolecular vibrational couplings.…”
Section: ⌬E 11mentioning
confidence: 89%